Molecular effects on spermatozoa of Mytilus galloprovincialisexposed to hyposaline conditions. Issue 6 (1st April 2019) - Lettieri, Gennaro; Maione, Martina; Ranauda, Maria Antonietta; Mele, Elena; Piscopo, Marina
Abstract: Salinity represents a critical environmental and an ecological factor in the reproduction of marine species. As global climate changes and anthropogenic factors affect salinity, in this study, we have analyzed the responses of Mytilus galloprovincialis spermatozoa to hyposaline stress. We exposed mussels, in laboratory tanks, for 24 hr at 18°C to control (35.9 psu) and three hyposaline (17.1, 22.6, and 26.2 psu) conditions, and evaluated the expression of sperm hsp70 and protamine‐like proteins genes. Further we analyzed the electrophoretic pattern, the DNA binding and the release from sperm nuclei of protamine‐like proteins. For all experimental approaches used, the results obtained at 17.1 psu condition were very similar to those obtained in the control condition, while alterations were always recorded at 22.6 and 26.2 psu conditions. Particularly, at 22.6 and 26.2 psu, was observed: 42.5‐ and 17.1‐fold increase in hsp70 expression, respectively, and hypoexpression of PL‐II/PLIV protamine‐like proteins genes. Further, electrophoretic mobility shift assays and salt‐induced release of nuclear proteins from sperm nuclei, revealed alterations in the PL proteins/DNA binding, in these two hyposaline conditions. The similarity between the results obtained in control and in the more severe hyposaline condition (17.1 psu) could indicate a phenomenon of fertility preservation strategy due to gamete plasticity. Abstract : The similarity in the Mytilus galloprovincialis spermatozoa response in control condition and in severe hyposaline condition (17.1 psu) could be due to gamete plasticity. Exposure to hyposaline condition as 22.6 and 26.2 psu cause changes in protamine‐like proteins properties and hyperexpression of hsp70 in M. galloprovincialis . Exposure to severe hyposaline condition as 17.1 psu does not affect protamine‐like proteins properties of M. galloprovincialis .